The magnitude of anemia and its associated factors among pregnant women in Hawela Tula Sub-city of Hawassa, Hawassa, Ethiopia - Tesfaye, Sileshi; Petros, Legese; Tulu, Israel Alemayehu; Feleke, Fentaw Wassie (Frontiers in Nutrition, 2024)
Introduction Anemia is one of the most serious health problems impacting people worldwide. The disease is quiet, moving slowly and producing only a few physical symptoms. Anemia during pregnancy raises the risk of premature birth, low birth weight, and fetal anomalies, and it can have a substantial financial impact on society and families. However, there was a paucity of studies on the magnitude and associated factors of anemia among pregnant women in southern Ethiopia. Objective This study aimed to assess the magnitude and associated factors of anemia among pregnant women attending antenatal care in the Hawella Tula Sub-city of Hawassa City in 2021. Methods Institution-based cross-sectional study was done on 341 randomly selected pregnant women attending antenatal care clinics. Data were obtained using a standardized semi-structured questionnaire. To identify the associated factors for the magnitude of anemia logistic regression model was used with an adjusted odds ratio (AOR) with 95% confidence intervals (CI) was calculated. Results The prevalence of anemia among pregnant women attending antenatal care in health facilities of Hawella Tula Sub-city was 113 (33.7%) with a 95% confidence interval (CI) (28.8, 38.9). Male-headed household (AOR = 2.217, 95% CI: 1.146, 4.286), rural resident (AOR = 3.805, 95% CI: 2.118, 6.838), early marriage below 18 years (AOR = 2.137, 95% CI: 1.193, 3.830), and recurrent of illness during pregnancy (AOR = 3.189, 95% CI: 1.405, 7.241) were associated factors for anemia. Conclusion Anemia prevalence among pregnant women was 113 (33.7%). Anemia among pregnant women was associated with rural residents, early marriage age below 18 years, and repeated illnesses during pregnancy.